FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM MEMBELI RUMAH (Studi kasus DI Perumahan Wijaya Indah Residence, Kuala Pembuang) - Hariyanto; Subehan (Jurnal Informasi, Perkebunan dan Sipil, 2021)
Housing is a group of houses that function as a residential or residential environment equipped with environmental facilities and infrastructure. With the fulfillment of daily needs, smooth work, or the fulfillment of other needs so as to provide satisfaction for residents. A sense of satisfaction or not with the occupants of the environment they live in will be felt after settling for some time and knowing the state of their place of residence. This study aims to determine the level of satisfaction of residents living in the housing. The benefits provided are as a consideration for housing developers to pay attention to the factors that consumers want. This study uses index analysis and calculation of validity and reliability tests with the IBM SPSS Statistics Version 24.0 program. the population in this study were residents of the Wijaya Indah Residence housing estate, Kuala Pembuang. While the sample used was 35 respondents with the Proportional Random Sampling method. Based on the analysis that has been used, it can be concluded that the variables of price, building location and environment together have a positive effect on purchasing decisions.